Social security, Covid-19 and the way forward: case of Malaysia - Mohd Safri Saiman; Salmie Jemon; Muhammad Puad Bebit; Mohd Ali Hindia (Universiti Malaysia Sabah, 2020)
Studies on social security in Malaysia can be traced back way in the early years of 2000s and has becoming even more interesting as the world economy opened to new ideas, challenges, and potentials. The labour market especially in developing and emerging economies are, prior to the devastative worldwide pandemic of COVID19, entangled with the sad but true impacts of the Industrial Revolution 4.0. Unfortunately, yet interestingly, the former seemed likely have the economy-wide impacts and implications for labour-related issues across the globe not excluding Malaysia that have policies targeted both domestic and migrant workers. In this paper, the authors aim to provide an updated overview of social security in Malaysia as the pandemic going through the series of overlapping wave of cases experienced by countries worldwide.